Chemically deposited nanocrystalline lead sulfide thin films with tunable properties for use in photovoltaics. (1st January 2015) - Slonopas, Andre; Alijabbari, Naser; Saltonstall, Christopher; Globus, Tatiana; Norris, Pamela
Abstract: A refurbished chemical bath deposition technique was developed for growing thin film semiconducting nanocrystalline lead sulphide (PbS) for use in photovoltaics. The goal of this work was to produce good quality crystals, with the high mobility of holes and electrons required for effective carrier separation in photovoltaic applications, and to control other electro-physical properties. Tightly attached, densely compacted, nanocrystalline PbS films with tunable electrical, physical, and optical properties were deposited. Adherence to the substrate was attained by establishing firmly attached kernels on the substrate from which crystallization occurred. Nanocrystalline structures were precipitated unto the substrate by controlling the deposition temperatures, time, concentration of the chemical constituents and ionic products. Using this approach nanocrystalline thin film PbS layers with controllable thicknesses were proliferated. SEM images show rigid crystalline structure, and low impurity concentrations in the film. Hall Effect and spectroscopy measurements illustrate tunable electrical, physical, and optical properties. Carrier concentrations were achieved between 6 × 10 16 /cm 3 −8 × 10 18 /cm 3 and mobility ranged between 3.4 cm 2 /Vs–33 cm 2 /Vs. Photoconductivity was measured using 980 nm laser and blackbody at temperature of 450 °C and 800 °C. Results indicate low recombination rates on the surface. Prolonged exposure to air confirms resistance to oxidation, and stability of the optical and electro-physical parameters.